2017
DOI: 10.2147/tcrm.s97619
|View full text |Cite
|
Sign up to set email alerts
|

Differential cardiovascular profiles of sodium-glucose cotransporter 2 inhibitors: critical evaluation of empagliflozin

Abstract: One of the most feared repercussions of type 2 diabetes mellitus is the risk of adverse cardiovascular outcomes. The current antidiabetic agents on the market have had difficulty in showing cardiovascular outcome improvement. The EMPA-REG OUTCOME trial studied the sodium-glucose cotransporter 2 inhibitor empagliflozin in type 2 diabetic patients at high risk of cardiovascular events. The trial results revealed a decrease in the composite primary end points of death from cardiovascular causes, nonfatal myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recent study comparing trial against real world data concluded that extrapolation of the trials and the results in the real world do not match [ 2 ]. Further research is needed to clarify and validate the benefits of SGLT2 at the translational biology level as well as its impact on clinical medicine [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing trial against real world data concluded that extrapolation of the trials and the results in the real world do not match [ 2 ]. Further research is needed to clarify and validate the benefits of SGLT2 at the translational biology level as well as its impact on clinical medicine [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM patients with CVD and peripheral vascular disease, we suggest the use of GLP1-RA as the data from LEADER and SUSTAIN-6 did not show any evidence of increased risk of amputation, unlike canagliflozin, which showed an almost double the risk of lower limb amputation [1517]. Fortunately, this risk has not been proved in any other studies of the SGLT2i including the DECLARE- TIMI 58 trial [28].…”
Section: Consensus Recommendations For the Management Of T2dm In Patimentioning
confidence: 99%
“…A recent study noted that the number needed to treat (NNT) to see a benefit in all-cause death compared favourably for empagliflozin against simvastatin or ramipril [103]. When published data for CV death, HHF and all-cause mortality were examined in a non-head-to-head illustrative comparison, SGLT2i therapies have favourable HF reductions compared with angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs), with each drug compared to placebo (Fig.…”
Section: Overcoming Treatment Comfort In Type 2 Diabetes Management: mentioning
confidence: 99%
“…SGLT2i treatments are well tolerated and have a favourable risk–benefit profile for many people with T2DM [1]. In practice, SGLT2i therapies appear to have a meaningful impact, with an NNT for several CVD outcomes similar to those of commonly prescribed drugs for the management and prevention of CVD [103].…”
Section: Maximising Benefits In the Treatment Of Type 2 Diabetes: Beymentioning
confidence: 99%